The Multisoliton Solutions for the (2+1)-Dimensional Sawada-Kotera Equation. (5th March 2013) - Xu, Zhenhui; Chen, Hanlin; Chen, Wei
Abstract : Applying bilinear form and extended three-wavetype of ansätz approach on the ( 2 + 1 ) -dimensional Sawada-Kotera equation, we obtain new multisoliton solutions, including the double periodic-type three-wave solutions, the breather two-soliton solutions, the double breather soliton solutions, and the three-solitary solutions. These results show that the high-dimensional nonlinear evolution equation has rich dynamical behavior.